Antidepressant-like activity of Bezafibrate in mice models of depression: a behavioral and neurobiological characterization - Xu, Dawei; Zhou, Jin; Zhou, Siyi; Wang, Weizhen; Wang, Chengniu; Jiang, Bo; Zhao, Wei (Frontiers in Pharmacology, 2025)
BackgroundDepression represents a major global public health challenge, inflicting profound suffering on patients while imposing substantial socioeconomic burdens on families and healthcare systems. Although monoamine-based antidepressants remain first-line pharmacotherapy, accumulating clinical evidence reveals several limitations of these medications, including delayed pharmacodynamics and low remission rates. Therefore, it is necessary to search for new drugs and develop effective strategies for depression treatment. Bezafibrate (BEZ), which can activate proliferator-activated receptor a (PPARα), exhibit various biological functions, such as improving mitochondrial function, reducing neuroinflammation, and improving cognitive function. This study is to explore whether BEZ has antidepressant-like effects and its potential mechanisms.MethodsThe antidepressant effects and potential mechanisms of BEZ were assessed by using forced swim test, tail suspension test, sucrose preference test, Western blot, gene interference, and immunofluorescence in the chronic unpredictable mild stress (CUMS) models of depression.ResultsResults showed that BEZ treatment significantly reversed depressive behavior in CUMS mice. The administration of BEZ obviously promoted the expression of PPAR, enhanced the BDNF signaling pathway, promoted hippocampal neurogenesis in CUMS mice. In addition, the pharmacologcial inhibitors GW6471 and K252a were obviously prevented the antidepressant effect of BEZ. Furthermore, gene knockdown of hippocampal PPARα or BDNF by using AAV-PPARα-shRNA-EGFP and AAV-BDNF-shRNA-EGFP, can remarkably inhibit the antidepressant effect of BEZ.ConclusionCollectively, the behavioral and neurobiological results demonstrate that BEZ exhibits antidepressant-like activity through PPARα/BDNF signaling pathway and may use as a potential antidepressant.